Effect of Supply Chain Innovation and Business Strategy Formulation in SME Clusters - Muhammad Farid Wajdi; Anton Agus Setyawan; Syamsudin Syamsudin; Ihwan Susila; Muzakar Isa (International Journal of Supply Chain Management, 2020)
Abstract— The purpose of this study is to analyze the effects of supply chain innovation and business strategy formulation to business performance. This study analyzes supply chain innovation and how SME compile their business strategy in industrial clusters.  Design of this study is quantitative. We develop a multivariate estimation model to analyze the relationship among constructs. We conduct surveys in 3 different SME clusters, they are shoes and sandals cluster in Mojokerto East Java, furniture cluster in Sukoharjo, Central Java and mushroom cluster in Yogyakarta. This survey includes 206 SME from three different clusters. Our result shows that supply chain innovation and business strategy formulation has positive effects on SME business performance. However, the result shows different magnitude on each of SME clusters. SME should improve their innovation in order to increase their business performance. Source of innovation is human capital, while empirically this is one of SME problems in Indonesia. Lack of qualified human capital encourages SME to conduct training with assistance from government and business partners. This study found that in Indonesia’s SME cluster there are difference business strategies. SME clusters uses two different strategies in their business policies, they are innovation and product development based on business partner strategies.